MANAGING MEDIA CAMPAIGNS - Jaeed, Hameed (ALBAHITH ALALAMI, 2008)
The most famous phenomena in the media administration, is the transfer of power, from the decision-makers inside the administration, especially those who occupy administrative positions by law, to those who enjoy a natural influence based on knowledge, skill and competence, especially on the psychological, political and social sides.The old way of dividing the administration into heads and hands is no longer accepted, and the separation of thinking and work based on a traditional format has become rather refused.Also, a chapter like this one might become a constant routine, but it doesn’t keep pace with the development of field concepts and practices of administrations. The logic of modern administration emphasizes the need to reconsider the responsibility of the decision-makers, and mastering new techniques, while respecting the conditions and forms of organizational structures, as well as coming up with new ideas from the practice of administering.